2015
DOI: 10.14257/ijgdc.2015.8.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Modularizing Legacy System through an Improved Bunch Clustering Method in Cloud Migration

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, the module dependency graph (MDG) on which the Bunch approach relies does not distinguish different dependencies. Taking the above problems into consideration, [3] improved the Bunch approach and adopted R-MDG, which can reflect different dependencies, as the input to make the results more practical.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the module dependency graph (MDG) on which the Bunch approach relies does not distinguish different dependencies. Taking the above problems into consideration, [3] improved the Bunch approach and adopted R-MDG, which can reflect different dependencies, as the input to make the results more practical.…”
Section: Related Workmentioning
confidence: 99%
“…If the system uses a common development framework, we will use the method presented in this article for component extraction. Otherwise, we will use the improved Bunch clustering algorithm for component extraction [3]. This paper is divided into five parts.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is implemented in the BUNCH clustering tool [7]. In [11], an improved BUNCH clustering is proposed for modularization of object oriented systems. It is shown that improved BUNCH clustering is able to produce clusters which are more stable with respect to benchmarks.…”
Section: Related Workmentioning
confidence: 99%
“…Incremental clustering is proposed in an attempt to accommodate newly introduced resources (orphan resources) in their appropriate subsystems and corrective clustering is proposed to accommodate structural changes (resource re-adoption). The orphan adoption approach has been adopted in many well-known reverse engineering tools [6,7,8,9,11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation